2009
DOI: 10.1007/s10295-009-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer with manipulated variables and its properties

Abstract: Cupriavidus sp. USMAA1020, a local isolate was able to biosynthesis poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] copolymer with various 4HB precursors as the sole carbon source. Manipulation of the culture conditions such as cell concentration, phosphate ratio and culture aeration significantly affected the synthesis of P(3HB-co-4HB) copolymer and 4HB composition. P(3HB-co-4HB) copolymer with 4HB compositions ranging from 23 to 75 mol% 4HB with various mechanical and thermal properties were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 23 publications
6
41
0
1
Order By: Relevance
“…Differential scanning calorimeter (DSC) (Pyris DSC, PerkinElmer) was used to determine the thermal properties of the terpolymer. This procedure was carried out according to Vigneswari et al [20]. The physical properties of the terpolymers were characterized using tensile machine (GOTECH A1-3000) to determine the tensile strength, Young's modulus, and elongation to break.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Differential scanning calorimeter (DSC) (Pyris DSC, PerkinElmer) was used to determine the thermal properties of the terpolymer. This procedure was carried out according to Vigneswari et al [20]. The physical properties of the terpolymers were characterized using tensile machine (GOTECH A1-3000) to determine the tensile strength, Young's modulus, and elongation to break.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…USMAA1020 was known to be a potential producer of copolymer P(3HB-co-4HB) [1]. In twostage fermentation, the strain was reported to be able to accumulate 75 mol% 4HB monomer while only 14 mol% 4HB was achieved in single-stage cultivation by using γ-butyrolactone as the sole carbon source [1,28]. It was concluded that in single-stage cultivation, the bacterium has the ability to accumulate high PHA content with lower 4HB molar fraction [1].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…The Mark-Houwink constant for polystyrene in chloroform was taken as K = 0.011 mL/ mg and α = 0.73, whereas those for P(3HB) in chloroform were taken as K = 0.016 mL/mg and α = 0.76 [19]. The mechanical test of PHA films were carried out in the form of dumbbell shapes (4 mm × 75 mm) using a Universal Testing Machine (GOTECH A1-3000 with U60 software, Taiwan) [28]. The thermal properties of the polymer films were determined using Pyris 1 differential scanning calorimetry (DSC) (Perkin Elmer, US).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The study on enzymatic degradation was carried out using depolymerase enzyme from Acidovorax sp as previously mentioned (Vigneswari et al 2009). The P(3HB-co-70 mol%4HB) films used had an initial weight of 0.011 g, film dimensions of 10 9 10 mm and thickness, 0.06 mm.…”
Section: Enzymatic Degradationmentioning
confidence: 99%